MAKNA AWLIYĀ’ DALAM AL-QUR’AN: Analisis Intertekstual terhadap Penafsiran M. Quraish Shihab dalam Al-Maidah 51: Satu Firman Beragam Penafsiran - M. Ali Fuadi Al-Ghifari; Miski Miski (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
M. Quraish Shihab in Al Maidah 51: Satu Firman Beragam Penafsiran – in addition to offering his interpretation of the meaning of awliya' – he also collected 40 interpretations tafseer scholars from their works. Given that each text is not independent and is always related to other texts, this study answered the main question: how is the influence of M. Quraish Shihab on other interpreters regarding the meaning of awliya' in Al Maidah 51: Satu Firman Beragam Penafsiran. In answering this question, the approach used was an intertextual approach As a result, it was found that the interpretation of M. Quraish Shihab related to the meaning of awliya' in Al-Maidah 51: Satu Firman Beragam Penafsiran was influenced by Ibnu ‘Āshūr, al-Ījī, Rashīd Riḍā, al-Shirāzī, al-Syawkānī, al‘Uthaymīn, Syaykh Ṭanṭawī, Syaykh al-Sha’rāwī, ‘Abd al-Qādir Shaybat al-Ḥaqq, alQāsimī, Hasbi al-Shiddīqī, al-Marāghī, al-Wāḥidī, al-Tabrisī, Wahbah al-Zuhaylī, al-Rāzī, Ibnu ‘Aṭiyyah, al-Zamakhsharī, Abū al-Sa’ūd, al-Alūsī, al-Qāsimī, Ibnu Taymiyyah, Ṭabāṭabā’ī, and al-Biqā’ī. In this case, M. Quraish Shihab's interpretation of the awliya' is in the sense of love (mawaddah), that is, just an ordinary relationship or business and the like are not automatically forbidden by Islamic doctrine, and Allah emphasizes the prohibition if what is established is a love relationship that can be hostile to Islam and wants evil for Muslims and good for opponents of Muslims.